Propagation and excitation of eigenmodes at isotropic-gyroelectromagnetic index-matched interfaces - Gigli, Miriam Laura (2004)
We study the relation between the excitation of eigenmodes at isotropic-gyroelectromagnetic flat interfaces under index-matching condition and the singular behaviour of the reflectivity at grazing incidences. We show that, as in the isotropic case, these eigenmodes can be excited by waves at other angles of incidence by introducing a periodic corrugation to the interface between the two media. The coupling produces strong peaks in the curves of reflectivity versus angle of incidence, whose intensity and shape depend on the height of the corrugation. Numerical examples for a particular orientation of the optic axis are presented. © 2004 Elsevier B.V. All rights reserved.